KEBEBASAN PERS DI INDONESIA PADA ERA REFORMASI DAN EKONOMI POLITIK MEDIA - Martono, Joko (Istek Widuri Jakarta, 2014)
Freedom of the press in Indonesia is guaranteed in the Act No. 40 of 1999. Variety article that relates to freedom of the press be substantially embodied the meaning is universal and tend to be liberal. For entrepreneurs, the existence of media institutions is seen as a land of business will bring profits. Therefore as the implications on the basis of the application of those concepts, information has become as valuable commodities exchange. The product is packaged in such a way the media become interchangeable merchandise and have economic value. A new outbreak of mass media companies marked increases the television industry in Indonesia has shown that